145 Stocker gains on diverse summer annual pastures. (28th November 2020) - Mercier, Kelly; Teutsch, Chris; Smith, Ray; Vanzant, Eric; Burdine, Kenny; Ritchey, Edwin
Abstract: The objective of this study was to determine if increasing forage botanical diversity improved stocker gains on warm-season annual (WSA) pastures. An opportunity exists to add extra gain on fall-born calves by grazing summer pastures after spring weaning and selling at a more favorable late summer market. However, cool-season perennial pastures in the Mid-South often have insufficient quality and yield to support desired summer gains. Therefore, the improved production and nutritive value of WSA forages shows promise in this system. A study was conducted near Princeton, KY, where calves (329, 366, and 297 kg in 2017, 2018, and 2019, respectively) grazed one of three WSA forage treatments without supplementation in a randomized complete block design with three replications. Treatments included 1) sorghum-sudangrass monoculture (MONO), 2) simple mixture (SIMPLE = sorghum-sudangrass, pearl millet, soybean), and 3) complex mixture (COMPLEX = SIMPLE + sudangrass, corn, crabgrass, cowpea, sunflower, sunn hemp, daikon radish, forage rape, Korean lespedeza). In 2017, MONO and SIMPLE calves had higher average daily gain (ADG) than COMPLEX calves (0.79 kg/day vs. 0.66 kg/day, P < 0.03). In 2018, no differences in ADG were detected among treatments (P > 0.3); however, calves only gained 0.01 kg/day. In 2019, MONO and SIMPLE calves again had higher ADG than COMPLEX calves (0.59 kg/day vs. 0.43 kg/day, P < 0.03). The exceptionally low 2018 ADG was likely due to the higher nutritional demand of heavier calves and the lower nutritive value of mature forages compared to other years. In conclusion, complex WSA forage mixtures did not offer any improvement in animal performance, and proper management of all WSA forages (maintaining a vegetative state) is paramount to achieving adequate gains on stockers without supplementation; however, supplementation may be necessary to improve WSA forage utilization in the rumen, potentially leading to more favorable gains.